The Potential Of Silicon Photonic Device Based On Tapered MMI Structure - Nor Syaimaa, Mohd Zamil; Hanim, Abdul Razak; Hazura, Haroon; Anis Suhaila, Mohd Zain; Fauziyah, Salehuddin; Siti Khadijah, Idris (Penerbit Universiti, UTeM, 2016)
Tapered multimode interference (MMI) structure has recently been utilized on multiple fabrications of the silicon photonics device. This type of structure has the potential for the production of small device for various applications. Various designs have been made in order to produce a compact design of MMI. This paper will discuss recent research on the different tapered MMI structure and its performances when simulating different structures (linear, parabolic, exponential and etc.). The use of tapered structure device allows wider waveguides separation, as compared to a straight MMI device.